2014
DOI: 10.3389/fnhum.2014.00157
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Freudian theory of sexual drives from a functional neuroimaging perspective

Abstract: One of the essential tasks of neuropsychoanalysis is to investigate the neural correlates of sexual drives. Here, we consider the four defining characteristics of sexual drives as delineated by Freud: their pressure, aim, object, and source. We systematically examine the relations between these characteristics and the four-component neurophenomenological model that we have proposed based on functional neuroimaging studies, which comprises a cognitive, a motivational, an emotional and an autonomic/neuroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
1
17
0
2
Order By: Relevance
“…Neural activity in amygdala and thalamus during sexual arousal is associated with a general feeling of pleasure [Walter et al, ], possibly induced by dopamine release in the midbrain, which projects to both thalamus and amygdala [Haber and Knutson, ]. It has further been proposed that these regions trigger the sexual‐cognitive processes by relevance detection and affective evaluation of sexual stimuli [Poeppl et al, ] and therefore relate to the motivational and emotional components of sexual arousal [Stoléru, ]. Equally related to these components is the anterior insula [Stoléru et al, ], where we also noted overlap.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Neural activity in amygdala and thalamus during sexual arousal is associated with a general feeling of pleasure [Walter et al, ], possibly induced by dopamine release in the midbrain, which projects to both thalamus and amygdala [Haber and Knutson, ]. It has further been proposed that these regions trigger the sexual‐cognitive processes by relevance detection and affective evaluation of sexual stimuli [Poeppl et al, ] and therefore relate to the motivational and emotional components of sexual arousal [Stoléru, ]. Equally related to these components is the anterior insula [Stoléru et al, ], where we also noted overlap.…”
Section: Discussionsupporting
confidence: 72%
“…These regions, however, are consistently deactivated during sexual arousal. This has been interpreted as concomitant impairment of metacognitive and self‐reflexive processing (TPJ) as well as release of intrinsic inhibition (STG) [Poeppl et al, ; Stoléru, ].…”
Section: Discussionmentioning
confidence: 95%
“…Sexual motivation in turn modulates excitability of motor cortices (Schecklmann et al, 2015), where we observed convergence of activation during sexual stimulation in women. This reflection of sexual motivation in motor cortex excitability provides evidence for motor preparation processes in sexual behavior in humans (Schecklmann et al, 2015; Stoléru, 2014). Convergent activity in the dACC and MCC should also contribute to sexual motivation given the connectivity of both structures with LPFC and premotor areas (Beckmann et al, 2009; Etkin et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…The basal ganglia hold strong structural and functional connections with motor areas (Draganski et al, 2008; Postuma, 2006). Corticobasal ganglia loops are believed to mediate the perceived urge to express sexual behavior and therefore sexual motivation (Kühn and Gallinat, 2011; Stoléru, 2014; Tanaka et al, 2004). Sexual motivation in turn modulates excitability of motor cortices (Schecklmann et al, 2015), where we observed convergence of activation during sexual stimulation in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation